Transformation of carbon dioxide into methanol - Ezzatul Ahmad, Nurjehan; Maizirwan, Mel; Murad, Fatin Nabilah; Ramli, Nur Amalina; Muhamad Sade, Zulaika; Ahmad Zailani, Ima Shahanaz; Rosmadi, Mohd Sharul Amri; Hamzah, Mohd. Salleh (Penerbit Akademia Baru, 2018)
Due to high potential of pollution risk of the untreated palm oil mill effluent (POME), it can be treated and converted into methane gas and with a further conversion that can produce into methanol. Previously, methanol is widely used in domestic and industrial applications as a solvent. It has a unique characteristic, which are colourless, flammable, volatile, odourless liquid that is readily miscible in water and has boiling point approximately 64.5˚C. Nowadays, the methanol has more been used in transportation and energy production. In future, it is predicted that the use of methanol in fuel applications will generate a huge demand. This study targets to design the process of transforming carbon dioxide, captured from the biogas through anaerobic digestion into synthesizing the methanol with the aim to produce 200 tonnes of methanol per year. This expectation is due to several advantages offered by the use of methanol, which less polluted to the environment, economically attractive, less flammable, high performance with high calorific value and thus become the focus of research nowadays.